The relationship between perceived causes of depression and desire for social distance in Farsi-speaking migrants and refugees from Iran and Afghanistan living in Germany. Issue 3 (26th June 2020) - Mobashery, Mahan; von Lersner, Ulrike; Böge, Kerem; Fuchs, Lukas; Schomerus, Georg; Franke, Miriam; Angermeyer, Matthias Claus; Hahn, Eric
Abstract : Purpose: An increasing number of migrants and refugees seeking asylum in Germany is challenging psychiatrists and psychotherapists in multiple ways. Different cultural belief systems on the causes of mental illness and their treatment have to be taken into consideration. The purpose of this study is to explore perceived causes of depression among Farsi-speaking migrants and refugees from Afghanistan and Iran, which represent two groups with a shared cultural heritage, but originating from very different regimes of mobility. Both are among the largest migrant groups coming to Germany over the past decade. Design/methodology/approach: In total, 50 Iranian and 50 Afghan migrants and refugees, who arrived in Germany in the past 10 years were interviewed, using an unlabeled vignette presenting signs and symptoms of depression. The answers were then coded through inductive content analysis. Findings: Among Iranians, there was a more significant number of causal attribution to Western psychiatric concepts, whereas Afghans attributed depression more often to the experience of being a refugee without referring to psychological concepts. These differences in attribution did, however, not affect the desire for a social distance toward depressed people. Nonetheless, a higher number of years spent in Germany was associated with less desire for social distance toward persons with depression among Afghans, but not among Iranians. Originality/value: To the best of the knowledge, this is the first study examining perceived causes of depression with Farsi-speaking migrants in Germany and contributes to understanding tendencies in the perception of depression in non-Western migrant groups.